Bridging the Divide Between the University and the High School - T. Hunter Strickland; Ashley Nolette (Study and Scrutiny)
In this article, an adolescent literacy and English education professor and a local high school English teacher describe the need to foster relationships together to build a better experience for secondary students and teacher candidates. Over the course of two semesters, both authors examine what their individual needs were, what steps were taken, and how programming was created for a fruitful partnership between a teacher preparation program and the title 1 high school down the street. Ultimately, both authors agreed that there was something missing in the separation of teacher preparation and what happens in actual English classrooms, and this partnership was created to build something better for all stakeholders involved.